Seismic mitigation effect for large-space underground structures considering spatially varying soil properties - He, Zhiming; Chen, Qingjun (Journal of Civil Engineering and Management, 2024)
The seismic response of the large-space underground structure (LSUS) is significantly influenced by the physical properties of the surrounding soil media, while the soil owns a strong spatial variability. This study proposes a seismic response analysis process of the soil-LSUS interaction system is proposed, which can consider the characteristic of the spatially distributed soil properties. The proposed process begins with establishing the spatially random field model of the soil properties using the improved latent space method. Then, the model is calibrated based on the real data and Bayesian approach, and the realization of the random field is accomplished. Further, the soil-LSUS interaction finite element (FE) model is established, which incorporating the soil physical properties generated from the random field. Finally, the nonlinear time-history analysis of the soil-LSUS interaction FE model is conducted. As an illustration of the proposed process, a typical LSUS located in Guangzhou is selected as an example, and the seismic mitigation measure which the lead-filled steel tube damper (LFSTD) is installed between the intermediate column and the top beam is adopted for the LSUS. The influence of the spatial variability of soil properties on the seismic mitigation effect of the LSUS is investigated. Results indicate that the spatial variability of the soil properties can cause a minor influence on the force and deformation of the intermediate column and the energy dissipation ratio between the LFSTD and structure, while it can bring a significant influence on the maximum deformation and force and the shape of the hysteresis loop of the LFSTD.